2016
DOI: 10.3855/jidc.7585
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress parameters and inflammatory and immune mediators as markers of the severity of sepsis

Abstract: Introduction: Sepsis is a complex inflammatory syndrome with diverse etiology and wide spectrum of severity. The aim of this study was to investigate whether inflammatory mediators, in comparison with oxidative parameters, are associated with severity of sepsis. Methodology: Plasma neopterin, adenosine deaminase (ADA), vascular cell adhesion molecule (VCAM), intracellular adhesion molecule (ICAM), interleukin (IL)-1, IL-6, and tumor necrosis factor alpha (TNF-α), as inflammatory mediators, and serum nitric oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 34 publications
2
17
0
10
Order By: Relevance
“…C reactive protein has a high sensitivity and specificity in diagnosing sepsis (up to 90% and 68%) and in some studies it seems to be even more reliable than procalcitonin 18. Variations in inflammatory parameters in patients with positive blood cultures have also been linked to different clinical outcomes 19 20. The algorithms used to evaluate the risk of whether a patient is septic are not reliable, with very low sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…C reactive protein has a high sensitivity and specificity in diagnosing sepsis (up to 90% and 68%) and in some studies it seems to be even more reliable than procalcitonin 18. Variations in inflammatory parameters in patients with positive blood cultures have also been linked to different clinical outcomes 19 20. The algorithms used to evaluate the risk of whether a patient is septic are not reliable, with very low sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in endotoxinderived animal and human sepsis models, TNF-α production is rapidly activated and can be measured in the plasma. [15,16] It was shown in a study that TNF-α could be a reliable indicator of severity of aggravation regardless of the etiologic factor of disease and as a prognostic factor. [17] Guo et al [18] found that the TNF-α levels were highest in the early period after injection (30 min to 1 h) in a sepsis model elicited by a lipopolysaccharide injection.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress mediated damage to mitochondrial DNA can lead to a cycle of ROS production and further mitochondrial damage. Also, the antioxidant system becomes completely overwhelmed and eventually cell death occurs, leading to multiple organ dysfunction (7)(8)(9). Recent reviews emphasize the importance of mitochondrialtargeted antioxidants in sepsis (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%